(3R,6E)-nerolidol, a fertility-related volatile secreted by the queens of higher termites (Termitidae: Syntermitinae) - Havlíčková, Jana; Dolejšová, Klára; Tichý, Michal; Vrkoslav, Vladimír; Kalinová, Blanka; Kyjaková, Pavlína; Hanus, Robert (Zeitschrift für Naturforschung. C, A journal of biosciences, 2019)
The queens of advanced social insects maintain their reproductive monopoly by using exocrine chemicals. The chemistry of these "queen pheromones" in termites is poorly known. We show that primary queens of four higher termites from the subfamily Syntermitinae (Embiratermes neotenicus, Silvestritermes heyeri, Labiotermes labralis, and Cyrilliotermes angulariceps) emit significant amounts of the sesquiterpene alcohol (E)-nerolidol. It is the dominant analyte in queen body washes; it is present on the surface of eggs, but absent in kings, workers, and soldiers. In E. neotenicus, it is also produced by replacement neotenic queens, in quantities correlated with their fertility. Using newly synthesised (3R,6E)-nerolidol, we demonstrate that the queens of this species produce only the (R) enantiomer. It is distributed over the surface of their abdomen, in internal tissues, and in the haemolymph, as well as in the headspace of the queens. Both (R) and (S) enantiomers are perceived by the antennae of E. neotenicus workers. The naturally occurring (R) enantiomer elicited a significantly larger antennal response, but it did not show any behavioural effect. In spite of technical difficulties encountered in long-term experiments with the studied species, (3R,6E)-nerolidol remains among eventual candidates for the role in queen fertility signalling.
Keywords: Animal Communication; Female; Sesquiterpenes; Social Behavior; fertilita; Animals; Pheromones; ženské pohlaví; seskviterpeny; komunikace zvířat; mužské pohlaví; Isoptera; feromony; sociální chování; zvířata; Fertility; Male